Implementation of Religious Character Education in Fostering Good Ahlaq at MTs Miftahussalam Probolinggo - Alfi Syahrin, Muhammad; Adiba Maulidiyah (Universitas Muhammadiyah Prof Dr Hamka, 2023)
The implementation of religious character education today is very necessary to overcome critical morals and foster good morals. Application is an effort to apply character education to students through several methods to achieve religious character. This study aims to describe and analyze the application of religious character building in fostering good morals in MTs Miftahussalam. The type of research used is qualitative field which is descriptive. This study used data collection techniques in the form of interviews, observations and documentation. The results showed that: 1. The implementation of religious character education in MTs Miftahussalam was carried out on: (a) integrated learning activities in each subject, and (b) outside learning activities carried out through school and culture. 2. In the application of the religious character building method, there are several means and factors that support the success of the method, namely: (a) Educator Commitment (b) Principal's Commitment (c) Procurement of Adequate Infrastructure 3. Supporting and inhibiting factors in implementing religious character education in MTs Miftahussalam (a) Supporting factors include: Family, teachers, environment, facilities, community (b) Inhibiting factors include: Family, school environment, information media, and community.